Economic Determinants of Agricultural Diversification and Their Impact on Household Food Security: Evidence from Haryana, India - Sharma, Simran; Shastri, Swati (Annals of Arid Zone, 2025)
Purpose- This study examines the economic factors affecting agricultural diversification and their relationship with household food security in Haryana, India. Design/methodology/approach- Data were collected from 400 farm households across 5 blocks of Kaithal using self-structured questionnaires. Simpson’s Diversity Index (SDI) measured diversification, and the Food Consumption Score (FCS) assessed food security. The Conditional Mixed Process Model (CMP) was used to jointly assess economic determinants of diversification and its impact on household food security, addressing endogeneity and providing robust standard errors. Findings- The study found an average SDI of 0.51, indicating moderate diversification. The mean FCS of 72 indicates acceptable food security. Factors positively influencing diversification included caste, landholding size, livestock count, agricultural subsidy, loans, and education. Access to storage facilities and hired labor negatively influenced diversification. Diversification showed a strong positive impact on household food security, with landholding size, education, livestock count, and loans also showing positive associations. Implications- Promoting agricultural diversification can enhance household food security in Haryana. Policies encouraging education, providing subsidies, and facilitating access to loans support diversification. Improving storage facilities and addressing the negative impacts of hired labor are crucial. Targeted policy interventions can foster economic stability, food security through diversified agricultural practices. Originality- This research provides insights into the economic determinants of agricultural diversification and their implications for household food security. It highlights the importance of promoting crop and livestock diversification to enhance food security in Kaithal, Haryana, offering significant implications for agricultural policy.